Análise das alternativas de proteção cambial para uma empresa multinacional do setor químico atuando no Brasil: uma discussão sobre modelo de proteção cambial com enfoque em custo para as operações de uma empresa importadora - Santos, Rafael Fernandes (2017)
This study addresses the practice of cash flow hedge operations within organizations, what are the main economic variables linked to the decision, instruments used, costs and benefits associated with the operation of an importing nature chemical company in Brazil. This issue is relevant because in an environment of high interest rates and exchange rate volatility it becomes increasingly challenging to make a decision regarding a currency protection model that minimizes its operational cost. The objective of this study is to identify a hedge model that minimizes the operational costs involved in this activity, taking into account the nature of the operation and the characteristics of the company’s cash flow. To achieve this, a study was conducted based on a quantitative experimental research approach that aimed to simulate the exchange rate hedge operations of the company using two types of financial instruments and comparing the costs of this simulation with the model that is being used in the last three years. The results contribute to the improvement of the management of the currency hedge in the company in question, through the proposed simulation and understanding of the main variables that can affect the price of the derivatives in order to reduce the operational cost of this activity in comparison with the current scenario.